EXPERIMENTAL INVESTIGATION OF THE FEASIBILITY OF CORNCOB ACTIVATED CARBON FOR ADSORBED NATURAL GAS STORAGE - Nelson Oghenenyore Peter; Wilfred Chinedu Okologume (Romanian Journal of Petroleum & Gas Technology, 2024)
In this study, activated carbon was synthesised from corn cobs through a two-step process involving carbonization at 600°C within an airtight furnace and chemical activation utilising phosphoric acid. The resultant activated carbon derived from corn cobs demonstrated significant adsorption capabilities, with a substantial BET surface area of 860.500 m2/g and exhibiting favourable adsorption-desorption kinetics. These attributes position it as an exceptional precursor material to produce nanoporous carbon materials suitable for the storage of natural gas. Two distinct sample sizes, measuring 841 microns and 400 microns, were meticulously chosen for examination in this investigation. The findings derived from the adsorption of natural gas, quantified in terms of volume-based metrics, revealed a direct and positive correlation between increasing pressures and pore sizes, resulting in higher adsorption capacities. The experimental conditions encompassed a temperature range of 27°C to 40°C, and storage pressures spanning from as low as 3.5 psi to as high as 28 psi. The recorded adsorption capacities were observed to fall within the range of 1.3424 mmol/g to 4.3073 mmol/g. The adsorption capacity of natural gas exhibited sensitivity to variations in both pressure and temperature, with the highest recorded storage capacity of 4.3073 mmol/g occurring at a temperature of 27°C and a pressure of 23 psi. The findings of this study highlight the significant potential of utilising corncob-derived activated carbon as an adsorbent for natural gas storage. Recommendations for further optimization and integration of this technology into existing gas storage systems are discussed. This research advances the prospect of utilising agricultural waste materials for eco-friendly and cost-effective energy storage, contributing to the transition towards a greener energy landscape.